Brief multidimensional self-control scale: psychometric properties and cross-gender measurement invariance of the Portuguese version - Pechorro, Pedro Fernandes dos Santos (Psychology, crime & law, 2025)
Self-control has been traditionally defined as the capacity to inhibit or overrule immediate urges in order to attain long-term goals, and it is considered an important topic of research in criminology and forensic psychology. The aim of the present study is to examine the psychometric properties of the Portuguese version of the Brief Multidimensional Self-Control Scale (BMSCS). Our sample consisted of 242 male and female participants (M = 30.19 years, SD = 12.78, range = 16–77 years) from Portugal. The one-factor model and the two-factor second-order model obtained adequate fits. Internal consistency/reliability, as measured by the alpha and omega coefficients, was adequate when considering the BMSCS total but the Inhibition and Initiation factors tended to present lower values. Convergent validity (with other self-control measures), divergent validity, and criterion-related validity (with justice-involvement and alcohol/drug abuse variables) were demonstrated. Measurement invariance across gender was established, with no significant differences being found when comparing male and female participants. Our findings add novel information and mostly support the use of the recently developed BMSCS as a short, valid, and reliable measure of self-control.